BERTUTUR SANTUN MELALUI TTL - Idah Hamidah (Universitas Diponegoro, 2014)
Abstract Courtesy ( politeness ) is one of the recalled strategies to maintain good relations between speaker and hearer . In this study, politeness is defined as the awareness of speakers will image the hearer; a concept called ‘the face’ (Brown and Levinson, 1987). To express politeness, one of which is realized with indirect speech act (TTL), for example, to declare a function directive, speakers can use direct speech (TL) with the imperative sentences and use TTL with declarative or interrogative sentences. This study aims to find a form of directive utterances in Japanese as well as politeness strategies. The benefit of this research is to provide choice to the learner how to speak Japanese, especially for express orders using TTL. Data obtained through the identification process to find speech that is suspected to contain commands mean. This step begins by identifying and marking the discourse in the form of dialogues that contains the event said directive . Directive speech is then transcribed (romanization) , which over the alphabet of Japanese characters into Latin letters. After transcription, triangulation to native speakers. Subsequently translation (transliteration) of the Japanese language as the source language (BS) into the Indonesian language as the target (BT). The translation process includes : (1) translation literally, is glossed words each forming the speech or discourse; (2) a free translation, the translation is bound context that focuses on BT. This is done so that the translation is communicative. Based on the results of the study found seven forms of expression TTL directive to express politeness in Japanese , namely : Form [ VTE ] , [ mashō ] , [ kara ] , [ te hoshii ] , [ yattorun ? ] , [ U / yo ] , and [ yoni suru shikanai ] . Keywords : command ; TTL ; politeness ; directive ; imperative